Mathematical Induction - Questions and Solutions
Question 2
Question 3 Important
Question 4
Question 5 Important
Question 6
Question 7 Important
Question 8 Important
Question 9
Question 10
Question 11 Important
Question 12
Question 13 Important
Question 14
Question 15 Important You are here
Question 16 Important
Question 17 Important
Question 18 Important
Question 19
Question 20
Question 21 Important
Question 22
Question 23 Important
Question 24 Important
Last updated at Dec. 16, 2024 by Teachoo
Question15 Prove the following by using the principle of mathematical induction for all n N: 12 + 32 + 52 + ..+ (2n 1)2 = (n(2n 1)(2n + 1))/3 Let P (n) : 12 + 32 + 52 + ..+(2n 1)2 = (n(2n 1)(2n + 1))/3 For n = 1, L.H.S = 12 = 1 R.H.S = (1(2 1 1)(2 1+ 1))/3 = (1(2 1) (2 + 1))/3 = (1 1 3)/3 = 1 Hence L.H.S. = R.H.S P(n) is true for n = 1 Assume that P(k) is true 12 + 32 + 52 + ..+ (2k 1)2 = (k(2k 1)(2k + 1))/3 We will prove that P(k + 1) is true. 12 + 32 + 52 + + (2(k + 1) 1)2 = ( (k + 1)(2(k + 1) 1)(2(k + 1)+ 1))/3 12 + 32 + 52 + + (2k 1)2 + (2k + 2 1)2 = ((k + 1)(2k + 2 1)(2k + 2 + 1))/3 12 + 32 + 52 + + (2k 1)2 + (2k + 1)2 = ((k + 1)(2k + 1)(2k + 3))/3 From (1) 12 + 32 + 52 + ..+ (2k 1)2 = (k(2k 1)(2k + 1))/3 Adding (2k + 1)2 both sides 12 + 32 + 52 + ..+ (2k 1)2 + (2k + 1)2 = (k(2k 1)(2k + 1))/3 + (2k + 1)2 = (k(2k 1)(2k + 1) + 3(2 + 1)^2)/3 = (2k + 1)((k(2k 1)+ 3(2 + 1))/3) = (2k + 1)((k(2k) k(1)+ 3(2 ) +3(1))/3) = (2k + 1)((2k^2 + 6 + 3)/3) = (2k + 1)((2k^2 + 5 + 3)/3) = (2k + 1)((2k^2 + 2 + 3 + 3)/3) = (2k + 1)((2k(k + 1) + 3( +1))/3) = (2k + 1)(((2k + 3)( +1))/3) = ((k + 1)(2k + 1)(2k + 3))/3 Thus, 12 + 32 + 52 + + (2k 1)2 + (2k + 1)2 = ((k + 1)(2k + 1)(2k + 3))/3 which is the same as P(k + 1) P(k+1) is true when P(k) is true By the principle of mathematical induction, P(n) is true for n, where n is a natural number